Cryptic Commonalities: Working Athwart Cryptography, Mathematics and Anthropology - Mannov, Adrienne; Oberborbeck Andersen, Astrid; Hojer Bruun, Maja (STS Encounters, 2020)
Based on ongoing interdisciplinary research about advances in a cryptographic technique called Secure Multiparty Computation (MPC), this article explores how research commonalities are carved out among mathematicians, engineers and anthropologists. STS scholars and anthropologists are increasingly engaged in research about and with data scientists and engineers, particularly as this relates to discrimination, surveillance and rights. Cryptography - a sub-genre of mathematics and often-invisible infrastructure enabling secure digital communication has received less attention. The article argues that the ubiquity of digital computing in our lives necessitates the creation of socio-mathematical vocabularies. Such vocabularies have the potential to lead to new situated data security practices based on local perceptions of rights and protection. STS scholars and anthropologists are uniquely situated to do this work. The article follows three anthropologists in their endeavors to find “cryptic commonalities” by “tacking back and forth” (Cf. Helmreich 2009) between mathematicians’, engineers’ and their own scientific vocabularies. Despite these attempts, however, the parties often “talk past each other”. Instead of shying away from the awkwardness that such moments produce, the authors embrace “epistemic disconcertment” (Cf. Verran 2013a), carving out a space in which they can communicate productively with each other. This space does not turn mathematicians into anthropologists or STS scholars into engineers, but it does make space for a shared scientific “pidgin” that enables collaboration (Cf. Galison 2010). With this pidgin, the authors walk the reader through the logics of MPC, and specifically, a cryptographic technique called “Shamir Secret Sharing” (Shamir 1979). In doing so, we join emerging voices in the crypto-community in an effort to develop cryptographic techniques for social good. This requires not just an understanding of the math, but also the social worlds impacted by these techniques.